Penerapan active learning untuk meningkatkan keterampilan passing atas pada pembelajaran bolavoli - Fauzy, Dyah Resti; Yulfadinata, Afifan; Ridwan, Mochammad; Ningish, Yuni Fitriyah; Prihanto, Junaidi Budi (Physical Education Departement of University PGRI Jombang, 2026)
This study aims to analyze the application of active learning methods to passing skills on bolavolley. The study used an experimental design with a Non-Randomized Control Group Pretest-Posttest Design. The research sample consisted of 64 students from MTsN 2 Sidoarjo, divided into an experimental group (n=32) and a control group (n=32). The research instrument was an overhead passing test with 10 attempts, where each success according to the criteria of technique and accuracy of the target was given a score of 1 (score range 0–10). The analysis results showed that the average score of the experimental group increased from 4.66 to 7.22, while the control group increased from 4.75 to 5.09. The paired sample t-test showed a significant increase in the experimental group (p = 0.000) and the control group (p = 0.003). Thus, the active learning method had a significant effect on improving volleyball passing skills. The independent sample t-test on the posttest showed a p-value of 0.0001 (<0.05), which means that there was a significant difference between the two groups. Volleyball learning through active learning is expected to increase student creativity and minimize waiting time for practice. Thus, the active learning method can be recommended as an alternative effective learning model in improving basic volleyball skills, especially overhead passing in physical education learning